A Panoramic History of Traditional Chinese Ethics - Linfeng Zhu (Journal of Dharma, 2024)
Is there a period in the history of ethical thought that most vividly captures humanity’s perception of morality? Can traditional ethical concepts provide meaningful insights into today’s economic, religious and political challenges? Yi-Ting Zhu addresses these profound questions in A Panoramic History of Traditional Chinese Ethics. This work explores the historical narratives preserved in digital archives, reflecting the economic, socio-political and religious conditions of ancient China. Spanning from the West Zhou Dynasty (1046–771 BC) to the Qing Dynasty (1616–1912), the book offers a comprehensive study of traditional Chinese ethics. Originally written in Chinese, this translated work consists of seven chapters, including an introduction, a brief chronology of Chinese history and a postscript. Beyond examining the development of Chinese ethical thought, the book also draws comparisons between Chinese and Western ethical traditions. Yi-Ting Zhu examines Chinese ethics through sociological and ideological frameworks, tracing its historical significance in contemporary discourse.